2002
DOI: 10.1177/154193120204602203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Distribution, Frequency, and Duration of Naturalistic Lane Changes

Abstract: This paper describes preliminary results of naturalistic lane change distribution, frequency, and duration data collected unobtrusively from 16 commuters using instrumented vehicles. The study was designed to improve upon previous data collection methods and support crash avoidance system development. A total of 8,667 lane changes (including unsuccessful maneuvers) were identified and classified in terms of severity, urgency, maneuver type, and success/magnitude. The total miles driven was 23,949 (38,542 km) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 1 publication
(2 reference statements)
0
36
1
Order By: Relevance
“…Younger drivers showed an increased frequency of glances towards the rear-view mirror and the blind spot when overtaking a slower vehicle (presumably a more complex manoeuvre performed at a higher speed than avoiding a static object). Compared to recent values obtained with on-the-road testing (Olsen et al, 2002;, the frequency of glances we are reporting look inflated. Indeed, Olsen and colleagues reported that 46% of the left-lane changes had a glance to the rear-view mirror, 53% to the left-side mirror and only 30% to the left blind spot.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Younger drivers showed an increased frequency of glances towards the rear-view mirror and the blind spot when overtaking a slower vehicle (presumably a more complex manoeuvre performed at a higher speed than avoiding a static object). Compared to recent values obtained with on-the-road testing (Olsen et al, 2002;, the frequency of glances we are reporting look inflated. Indeed, Olsen and colleagues reported that 46% of the left-lane changes had a glance to the rear-view mirror, 53% to the left-side mirror and only 30% to the left blind spot.…”
Section: Discussioncontrasting
confidence: 86%
“…For instance, Robinson et al (1972) reported that the first search is towards the left-side mirror in 70-80% of lane changes, and that the number of glances increases with increased traffic density. More recently, Wierwille and collaborators conducted an extensive analysis of on-the-road glances of experienced drivers during the 3-s period preceding lane changes (Olsen, Lee, & Wierwille, 2002;. They reported glance durations of 2.4 s with 46% of the left-lane changes having a glance to the rear-view mirror, 53% to the left-side mirror and only 30% to the left blind spot.…”
Section: Introductionmentioning
confidence: 99%
“…Left and right lane changes were considered separately. Previous work has shown that opposite ROI to the lane change direction are rarely, if ever, inspected (Olsen et al, 2002(Olsen et al, , 2005. Therefore, only the external mirror and blind spot respective to the lane change direction were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Older drivers showed a lower frequency of glances toward the side mirror and blind spot compared to younger drivers. A number of studies (Henning, Scweigert, Baumann, & Krems, 2006;Kiefer & Hankey, 2008;Olsen, Lee, & Wierwille, 2002Robinson, Erickson, Thurston, & Clark, 1972) have assessed drivers' visual search during lane changes under highway conditions. To the best of our knowledge, however, this pattern of reduced mirror use in older drivers prior to lane changing observed by Lavallière et al (2007) has not been quantified under actual highway driving conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The trajectory accommodates a changing velocity v, and the change time t 1 was made inversely proportional to the move urgency, centered on a mean maneuver time of 6.2 seconds (Olsen et al 2002). The lane change models are updated in the simulation every 10 ms.…”
Section: Lateralmentioning
confidence: 99%